The Reception Analysis of the Content of Many Children Many Sustenance on Instagram @Magdaleneid - Sianturi, Nella Saputri; Robin, Patricia (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Social media is interactive, allowing people to interact with each other and have the right and freedom to express themselves. One of the uploads on Instagram social media @magdakeneid regarding a statement by a content writer who explained that the saying 'Many Children Many Sustenance' is no longer relevant today. This content has various opinions, especially for women. This study wants to determine how the audience understands and accepts content that contradicts the saying 'many children many sustenance' on social media. This study aims to determine the audience's understanding and acceptance of the content “Not All Women Relate to the Proverb Many Children Many Sustenance, Including Me” on Instagram @magdaleneid. This research uses qualitative research methods by conducting interviews with eleven informants from the audience who are mothers who follow and read @magdaleneid Instagram posts with different socio-cultural backgrounds. The data obtained was then analyzed using Stuart Hall's reception analysis method. The research shows that there are various interpretations of the audience in interpreting the content “Not All Women Relate to the Proverb Many Children Many Sustenance, Including Me” based on their social and cultural backgrounds. In this study, it can be seen that 9 out of 11 sources are in the dominant hegemonic position, 1 source is in the negotiated position, and 1 source is in the oppositional position. The positions chosen by the informants based on their respective opinions also show that contextual factors influence the audience's acceptance of media texts. This research is expected to build public awareness of the impact of social media in disseminating and promoting certain messages, including proverbs or narratives related to gender and family issues.